Acute inflammatory neuropathy with monoclonal anti-GM2 IgM antibodies, IgM-κ paraprotein and additional autoimmune processes in association with a diffuse large B-cell non-Hodgkin's lymphoma. (21st January 2013) - Milnik, Annette; Roggenbuck, Dirk; Conrad, Karsten; Bartels, Claudius
Abstract : Lymphoproliferative disorders are often associated with autoimmune processes preceding or following the occurrence of a lymphoma. Here, we describe a patient with a history of recurrent diffuse large B-cell non-Hodgkin's lymphoma who suffered from an acute inflammatory neuropathy with specific monoclonal anti-GM2 IgM antibodies and associated IgM-κ paraprotein. It was possible in this case to prove that both, anti-GM2 IgM antibodies and IgM-κ paraprotein, share the same binding characteristic. In addition, the patient possibly suffered from an immune thrombocytopenia and an early-stage bullous pemphigoid with anti-BP-230 IgG antibodies. Intravenous immunoglobulin and plasmapheresis alleviated the acute neuropathy and thrombocytopenia, while the bullous pemphigoid has been aggravated. In summary, the simultaneous occurrence of multiple autoimmune processes was a sign of a dysfunctional immune system preceding the relapse of a B-cell non-Hodgkin's lymphoma.